An original framework for strategic technology development of small manufacturing enterprises in emerging economies. Issue 2 (12th December 2019) - Nanda, Tarun; Gupta, Himanshu; Singh, Tejinder P.; Kusi-Sarpong, Simonov; Jabbour, Chiappetta Jose Charbel; Cherri, Adriana
Abstract : Purpose: Technology and knowledge have become the buzzwords of the new millennium. Technological changes and demanding customers are creating a more knowledge intensive, turbulent, complex and uncertain environment. Organizations, which are able to continually build faster and cheaper new strategic assets than their competitors, create long-term competitive advantages. Thus, the growth of companies is directly associated with innovativeness and technological development, especially for small organizations that are more vulnerable to dynamic changes in market place. Organizations need a strategic framework that can help them to achieve the goal of technology development and competitiveness. The purpose of this paper is to develop such strategic framework for small organizations for their technology development and, hence, survival in marketplace. Design/methodology/approach: Options field methodology, options profile methodology, analytic hierarchy process (AHP) and fuzzy set theory are utilized to generate various options and profiles to propose a conceptual framework for technology development. Findings: The results from the study showed that "mixed approach, " "strategic simulation approach" and the "regulatory environment approach, " in this order, emerged as the top three important options for the strategic technological development of small manufacturing enterprises. Originality/value: This result can provide an original and more accurate implementation pathway toward technological innovative development in emerging economies. The proposed framework can provide valuable guidelines and recommendations to practicing managers and analysts for policy development to promote innovative and technological developments.